Malaria and Helminth Coinfection among Children at the Douala Gyneco-Obstetric and Pediatric Hospital - Ashungafack Flavio; Yamssi Cedric; Noumedem Anangmo Christelle Nadia; Vincent Khan Payne (Journal of Tropical Medicine)
Background. Malaria and helminth infections are major public health issues in sub-Saharan Africa including Cameroon. This study was aimed at determining the prevalence and risk factors associated with malaria and helminth coinfection among children in the Douala Gyneco-Obstetric and Pediatric Hospital (HGOPED) in Douala, southwestern Cameroon. Material and Methods. The study was a hospital-based cross-sectional study that took place from January to July 2020 where 203 children were involved. Blood samples were collected from the children and thick blood smears were prepared and examined microscopically for malaria parasites. Stool samples were also collected and examined through the Kato-Katz technique for the identification of helminth eggs. Demographic and socioeconomic data and information of participant’s knowledge on the transmission of malaria and helminth infections were collected with the use of a well-structured questionnaire. Results. The overall prevalence of P. falciparum infection was 28.8%, while the overall prevalence of helminth was 9.36%. The only species of helminth identified were Ascaris lumbricoides and Trichuris trichiura with a prevalence of 4.26% and 2.95%, respectively, and mixed infection of both A. lumbricoides and T. trichiura with a prevalence of 1.47%. Coinfection of malaria and helminth was observed with a prevalence of 6.90%. Associations of malaria-helminth coinfection with age groups, parent’s educational level, type of latrine, and source of water factors were not statistically significant (p>0.05), while the prevalence of the coinfection with respect to parent’s occupation, presence of stagnant water around homes, washing of hands after using the toilet, and washing of fruits before eating was statistically significant (p<0.05). Conclusion. The findings suggest that helminths and malaria infections tend to occur in children. Not washing hands after using the toilet, not washing fruits before eating, the presence of stagnant water around homes, and parents’ occupation were found to be strongly associated with coinfection. Health education on the importance of better sewage disposal, draining of stagnant water around homes, and other sanitary practices is recommended.